Improving the legal status of the State Guard Department of Ukraine as a military formation - Shakun, V. I.; Kuznetsov, V. V.; Syiploki, M. V. (Аналітично-порівняльне правознавство, 2025)
The article examines the legal status of the State Guard Department of Ukraine. The concept and characteristics of military formations are analyzed. It is established that discussions continue in military law doctrine regarding the definition of the concept of “military unit” and the characteristics of this concept. The conclusion is justified that the normative concept of “military unit” is abstract and does not cover all the characteristics that characterize this category. The hypothesis is expressed that legislation and doctrine formulate the concept of “military unit” as a component of the Armed Forces of Ukraine, leaving out other military formations formed in accordance with the laws of Ukraine. Based on an analysis of regulatory legal acts, it has been established that the personnel of the State Guard Department of Ukraine consist of military personnel serving under contract and conscripts. The article concludes that the State Guard Department of Ukraine is also designed to protect the sovereignty of Ukraine, state independence and national interests, territorial integrity and inviolability in the event of armed aggression, armed conflict or threat of attack by directly conducting military (combat) operations. Using a comparative method to compare the characteristics of a military formation and those of the State Guard Department of Ukraine, the authors of the article have drawn the following preliminary conclusions: a) The State Guard Department of Ukraine is a military unit characterized by a single chain of command, military discipline, a clear vertical hierarchy, and centralized management; b) the State Guard Department of Ukraine has an established procedure for military service; c) the activities of the State Guard Department of Ukraine are regulated not only by the Constitution of Ukraine, laws, and other regulatory acts binding on all state bodies, but also by departmental orders, directives, instructions, and guidelines; d) military personnel of the State Guard Department of Ukraine have a special status related to the specifics of military. It has been concluded that the State Guard Department of Ukraine should be classified as “other military formations established in accordance with the laws of Ukraine”.